Cure kinetics characterization of soy‐based epoxy resins for infusion moulding process. (20th May 2016) - Subbiah, Rajkumar; Tjong, Jimi; Nayak, Sanjay K.; Sain, Mohini
Abstract: This study presents the kinetics of the reaction of diglycidyl ether of bisphenol A (DGEBA) based epoxy resin in the presence of epoxidized soybean oil (ESO) cured with triethylene tetramine (TETA). An isothermal differential scanning calorimetric (DSC) study is carried out to propose a model to analyze the cure kinetics of bio‐based resin. The proposed model is also compared with the Kamal model. The results clearly highlight that the proposed model attains a reasonable percentage of improvement in predicting cure data. Adding ESO to the conventional system decreases the reaction enthalpy and increases the activation energy of the system. The outcome of the study confirms the feasibility of the proposed material system for an infusion process. Further, tensile property improvement is obtained through using an infusion process for the proposed material system.